A single-domain antibody detects and neutralises toxic Aβ42 oligomers in the Alzheimer’s disease CSF - Bigi, Alessandra; Napolitano, Liliana; Vadukul, Devkee M.; Chiti, Fabrizio; Cecchi, Cristina; Aprile, Francesco A.; Cascella, Roberta (Alzheimer's research & therapy, 2024)
Background Amyloid-β 42 (Aβ 42 ) aggregation consists of a complex chain of nucleation events producing soluble oligomeric intermediates, which are considered the major neurotoxic agents in Alzheimer’s disease (AD). Cerebral lesions in the brain of AD patients start to develop 20 years before symptom onset; however, no preventive strategies, effective treatments, or specific and sensitive diagnostic tests to identify people with early-stage AD are currently available. In addition, the isolation and characterisation of neurotoxic Aβ 42 oligomers are particularly difficult because of their transient and heterogeneous nature. To overcome this challenge, a rationally designed method generated a single-domain antibody (sdAb), named DesAb-O, targeting Aβ 42 oligomers. Methods We investigated the ability of DesAb-O to selectively detect preformed Aβ 42 oligomers both in vitro and in cultured neuronal cells, by using dot-blot, ELISA immunoassay and super-resolution STED microscopy, and to counteract the toxicity induced by the oligomers, monitoring their interaction with neuronal membrane and the resulting mitochondrial impairment. We then applied this approach to CSF samples (CSFs) from AD patients as compared to age-matched control subjects. Results DesAb-O was found to selectively detect synthetic Aβ 42 oligomers both in vitro and in cultured cells, and to neutralise their associated neuronal dysfunction. DesAb-O can also identify Aβ 42 oligomers present in the CSFs of AD patients with respect to healthy individuals, and completely prevent cell dysfunction induced by the administration of CSFs to neuronal cells. Conclusions Taken together, our data indicate a promising method for the improvement of an early diagnosis of AD and for the generation of novel therapeutic approaches based on sdAbs for the treatment of AD and other devastating neurodegenerative conditions.